2016
DOI: 10.1002/jsfa.7651
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of iron bioavailability from fortified pearl millet based weaning food

Abstract: Overall, bioavailability of electrolytic iron could be improved by supplementation of vitamin A, and this mixture can be considered as a useful fortificant for pearl millet based complementary foods fortification designed to prevent iron deficiency. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The sales volume is expected to nearly double in India from 334.4 ml in 2016 to 657.2 ml by 2021 and the market is likely to be worth over $1.6 billion by then (Anon 2017); suggesting a wide scope of omega-3 fortification in such product. Previous studies have demonstrated that fortification is one of the best approaches to combat macro and micronutrient deficiencies (Sihag et al 2016;Goyal et al 2016aGoyal et al , 2017. A very few studies are available on the fortification of flaxseed oil in ice cream and frozen desserts.…”
Section: Introductionmentioning
confidence: 99%
“…The sales volume is expected to nearly double in India from 334.4 ml in 2016 to 657.2 ml by 2021 and the market is likely to be worth over $1.6 billion by then (Anon 2017); suggesting a wide scope of omega-3 fortification in such product. Previous studies have demonstrated that fortification is one of the best approaches to combat macro and micronutrient deficiencies (Sihag et al 2016;Goyal et al 2016aGoyal et al , 2017. A very few studies are available on the fortification of flaxseed oil in ice cream and frozen desserts.…”
Section: Introductionmentioning
confidence: 99%
“…In many low‐ and middle‐income countries, contamination of complementary foods is one of the major factors that compromise the nutritional outcome of complementary feeding largely due to the occurrence of diarrheagenic foodborne diseases caused by nontyphoidal Salmonella and Escherichia coli among others (Scallan et al, 2015 ). As such, complementary feeding of children with safe food becomes a prerequisite for reducing diarrheagenic foodborne diseases and consequently attaining optimal growth among children (Sihag et al, 2015 ). Evidence in the literature shows that local production of safe complementary foods and their utilization necessitates that caregivers practice hygienic food behavior (Kunadu et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%